PENGEMBANGAN MEDIA LUDOKU PADA PEMBELAJARAN IPAS SISWA KELAS V SD NEGERI 1 SIDOHARJO - Nurlia Ningsih, Mita; Krisnawati, Yuni; Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to develop valid, practical, and effective Ludoku media for science learning for fifth-grade students of SD Negeri 1 Sidoharjo. This research method uses the Research and Development (R&D) method with the ADDIE development model. The research subjects were fifth-grade students of SD Negeri 1 Sidoharjo. Data collection techniques included observation, interviews, questionnaires, tests, and documentation. Data analysis techniques use media validity analysis, ludoku media practicality analysis, and ludoku media effectiveness analysis.Based on the research results, namely the analysis of the Ludoku media validation test assessed by three experts: a linguist who met the criteria for very valid with an average score of 0.93, a media expert who met the criteria for very valid with an average score of 0.92, and a material expert who met the criteria for very valid with an average score of 0.95. Meanwhile, the analysis of the teacher and student practicality assessment sheets showed that the Ludoku media met the criteria of being very practical with an average score of 97.47%. Furthermore, the analysis of the effectiveness assessment obtained an N-gain score with an average of 0.71, categorizedin the high. Based on the research results, it can be concluded that the Ludoku media is proven to be valid, practical, and effective, making it suitable for use in the learning process in grade V of SD Negeri 1 Sidoharjo